ANALISIS FAKTOR DETERMINAN YANG MEMPENGARUHI POLA KONSUMSI MAHASISWA NOBEL INDONESIA MAKASSAR YANG BERTEMPAT TINGGAL DI KOS - Sri Prilmayanti Awaluddin; Rahmatia Rahmatia (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
The Determination Factor Analysis Research that has Influenced the Consumption Pattern of Makassar Indonesian Nobel Students Living in Kos with the aim to find out simultaneously the influence of Allowances, Scholarships, Savings and Gender on the Consumption Patterns of Makassar Indonesian Nobel Students in Makassar. This research uses quantitative methods, namely multiple linear regression. The data of this study uses primary data in the form of data about the characteristics of respondents obtained by direct interviews using questionnaires by containing several questions related to the dependent variables used and secondary data in the form of data obtained indirectly to obtain student data obtained from online portals STIE Nobel Indonesia Makassar and the database of the Indonesian Nobel Makassar Accounting and Management Department. The variable (X) is in the form of allowance, variable (D) is in the form of Scholarship, Savings, Gender and variable (Y) is in the form of consumption. The population of this research is the students of all Makassar Nobel Indonesia students who live in boarding houses. The sampling technique used in this study was purposive sampling. The sample criteria used are Nobel Indonesia Makassar students who live in boarding houses near the campus and easily accessible. The number of samples in this study were 126 respondents. The analytical method used in this study is multiple linear regression analysis using SPSS version 21. The results show 1). Allowance (X1) has a positive and significant effect on the consumption patterns of Makassar Indonesian Nobel students who live in boarding houses (2). Scholarship (D1) has a positive and significant effect on the consumption patterns of Makassar Indonesian Nobel students who live in boarding houses. (3). Savings (D2) does not affect the consumption patterns of Makassar Nobel Indonesian students who live in boarding houses. Gender (D3) does not affect the consumption patterns of Makassar Indonesian Nobel students who live in boarding houses. The linear regression equation obtained Y = 3,910 + 0,698 X1 + 0,653 D1 - 0,051 D2 + 0,066 D1 + ????µ